SOSIOLINGUISTIK DALAM PROSES PEMBELAJARAN BAHASA SERTA KAITANNYA DENGAN PENDIDIKAN BAHASA ARAB - Habibah, Ihda Filzafatin; Fahmi, Alif Anharul; Fitrah, Isti Jayang; Ichwani, Imron; Wargadinata, Wildana (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
In the field of education, sociolinguistics plays a crucial role in language acquisition, particularly in the learning of Arabic. Sociolinguistics is a combination of linguistic and social terms that refers to a field of study examining the interaction between language, human behavior, society, and the mind. According to sociolinguistics, the language used must be structured and possess good grammatical components. Contemporary learners have undergone various developmental phases in language learning, depending on the setting of their language development. The purpose of this article is to describe sociolinguistics and its relevance to Arabic language learning. The development of first and second languages in individuals will be the next topic to be discussed. Additionally, this article will also explore guidelines for teaching a second language and approaches to learning the process through the first language. The methodology employed in this research is qualitative. Through literature survey, data was collected using content analysis approach. Information gathered from books, magazines, and articles related to the research object. Keywords: Sociolinguistics, Language Learning Process, Arabic Language